PENGARUH KUALITAS SERVICE EXCELLENCE DAN PENANGANAN KELUHAN TERHADAP KEPUASAN NASABAH PADA PT BANK PEMBANGUNAN DAERAH BALI CABANG TABANAN - Ni Luh Gede Putri Wangi Natasya; I Nyoman Suka Sanjaya; Kasiani (CV. Lafadz Jaya, 2026)
Customer satisfaction is an important factor in the banking industry because it reflects customers' perceptions of service quality and influences long-term relationships with the bank. This study aims to analyze the effect of Service Excellence and Complaint Handling on customer satisfaction at PT Bank Pembangunan Daerah Bali Tabanan Branch.This study employed a quantitative research approach with a survey method. The sample consisted of 100 customers selected using purposive sampling. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics. This research is based on the Expectation Confirmation Theory, which explains that customer satisfaction is achieved when the services provided meet or exceed customer expectations.The results show that Service Excellence has a positive and significant effect on customer satisfaction. Complaint Handling also has a positive and significant effect on customer satisfaction. Simultaneously, both variables significantly influence customer satisfaction at PT Bank Pembangunan Daerah Bali Tabanan Branch. This study concludes that improving service quality and implementing effective complaint handling can enhance customer satisfaction. Therefore, the bank is expected to continuously improve its service performance and complaint handling process to maintain customer satisfaction and strengthen customer trust.